Blaski i cienie życia w internatach szkół jezuickich w II Rzeczypospolitej - Puchowska, Małgorzata (Biuletyn Historii Wychowania, 2012)
Jesuit boarding schools did not fulfil only social roles. They were educational institutions shaping discipline, morality and religiousness of their pupils. The monks organized various activities for their students which were conducive for acquiring and consolidating knowledge. Students’ time was filled with the review of school material, literary exercises, debates or production of theatre performances. The offer depended on the degree of exclusivity of a given establishment. In the Second Republic of Poland, there functioned three Jesuit schools for laymen: in Khyriv (Pol. Chyrów), Vilnius and Gdynia. Only the first two ran boarding schools. Both boarding schools offered very good living conditions, and the life of the alumni passed according to a similar, clearly defined day rhythm. The institutions in busy urban Vilnius and peripheral Khyriv were very much different. The educational process used for the boarding students from Vilnius lacked special rigours, which was different from the methods generally accepted at that time. The behaviours of boarding students from Khyriv, in turn, were regulated in the minutest detail by Statutes and regulations and the system of punishments was very elaborate. The schools tried to restore order by the method of overcoming the resistance of the more independently feeling and thinking pupils.